2008
DOI: 10.1017/s1751731108001808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-weaning concentrate feeding on calf performance, carcass and meat quality of autumn-born bull calves weaned at 90 or 150 days of age

Abstract: A study was conducted to evaluate the effect of pre-weaning concentrate feeding in early-weaned (EW, day 90) or traditionally weaned (TW, day 150) autumn-born beef calves on growth, feed intake and feed efficiency, and carcass and meat quality. Twenty-eight male calves were either EW or TW, and offered a starter concentrate (S) or no additional feed (NS) during the pre-weaning period. Therefore, four management strategies were tested: EWS, EWNS, TWS and TWNS. Growth patterns were affected by management strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
5
9
1
2
Order By: Relevance
“…Meat from young animals is supposed to have greater L* and lower H* values than that of older animals fed similar diets. Older calves have similar L*, but hue angle, redness and chroma values are greater Blanco, Villalba, Ripoll, Sauerwein, & Casasús, 2008;Blanco, Villalba, Ripoll, Sauerwein, & Casasús, 2009;Insausti et al, 2001) than the present results. Casasús, Ripoll, and Albertí (2012) also reported that yearlings fed corn silage had chroma values between 20 and 18 from 1 to 13 d, greater values than obtained in veal in the present experiment.…”
Section: Effect Of the Management System On Color Evolution Of Meatcontrasting
confidence: 74%
“…Meat from young animals is supposed to have greater L* and lower H* values than that of older animals fed similar diets. Older calves have similar L*, but hue angle, redness and chroma values are greater Blanco, Villalba, Ripoll, Sauerwein, & Casasús, 2008;Blanco, Villalba, Ripoll, Sauerwein, & Casasús, 2009;Insausti et al, 2001) than the present results. Casasús, Ripoll, and Albertí (2012) also reported that yearlings fed corn silage had chroma values between 20 and 18 from 1 to 13 d, greater values than obtained in veal in the present experiment.…”
Section: Effect Of the Management System On Color Evolution Of Meatcontrasting
confidence: 74%
“…By contrast, the major fatty acid group in the TL cut was SFA (44.09 g/100 g of FAME), followed by MUFA (43.11 g/100 g of FAME) and PUFA (12.80 g/100 g of FAME). Blanco et al . and Ripoll et al .…”
Section: Resultsmentioning
confidence: 96%
“…Plasma IGF‐I was analysed through solid‐phase enzyme‐labelled chemiluminiscent immunometric assay (Immulite®; Siemens Medical Solutions Diagnostics Limited, Llanberis, Gwynedd, UK). Bovine plasma samples previously analysed through a commercial enzyme immunoassay kit (Blanco et al., 2008) were re‐assayed to evaluate the accuracy of the analysis. A regression analysis was performed to compare the results obtained with both methods ( r = 0.96).…”
Section: Methodsmentioning
confidence: 99%